New insight into the taxonomy of Cephaloziellaceae (Marchantiophyta): the family of the smallest higher plants on Earth - Bakalin, Vadim A.; Maltseva, Yulia D.; Klimova, Ksenia G.; Nguyen, Van Sinh; Choi, Seung Se; Troitsky, Aleksey V. (Frontiers in Plant Science, 2024)
An analysis of the phylogeny of Cephaloziellaceae was carried out based on trees constructed for previously and newly obtained sequences of five genes, nuclear ITS1-2 and chloroplast trnL-F, trnG, rbcL, and psbA. Phylogenetic trees inferred from different genes are congruent for the main details; however, the position of several taxa is variable. As a result, a new phylogenetic system of the family is proposed. The narrow genus concept seems to be more appropriate for the family. Cephaloziella spinicaulis is segregated into the new genus Douiniella, the generic status for Prionolobus and Metacephalozia is confirmed, and the dubious generic status of Kymatocalyx is substantiated. The generic independence of Cylindrocolea from Cephaloziella s. str. is confirmed. The small amount of data hinders the description of two more genera from Cephaloziella s.l. generic name Cephaloziella (Spruce) Schiffn. became widely known. Moreover, the number of known species was so significant that, despite the earlier appearance, the name Cephaloziella was assigned nom. cons. with priority over Dichiton published 40 years before. The purposeful study of Cephaloziella began with Spruce (1882), who assigned the taxonomic status of this group of plants to Cephalozia subg. Cephaloziella Spruce and subg. Prionolobus Spruce (Spruce, 1882). After 11 years, this subgenus was elevated to the rank of genus by Schiffner (1893): Cephaloziella (Schiffner, 1893). Schiffner also recognized Prionolobus (Spruce) Schiffn., which is actually the evaluated Cephalozia subg. Prionolobus.A remarkable new step in the knowledge of Cephaloziellaceae was made by Douin, who segregated this family (Douin, 1920) and perfectly described the features differentiating Cephaloziaceae and Cephaloziellaceae. In addition, he also accepted (described or re-evaluated) the following genera within Cephaloziellaceae: Dichiton, Lophoziella Douin (where the type species is the same as that of Dichiton), Prionolobus, Evansia Douin et Schiffn. (illegitimate name, later homonym of Evansia Salisb. ex Decne.), Cephaloziella and Protocephaloziella Douin. The next major contribution to the knowledge of Cephaloziellaceae taxonomy was made by Schuster (several works, with the fundamental one published in 1972) (Schuster, 1972). Schuster described the following genera: